Polydopamine films: Versatile but interface-dependent coatings - Ball Vincent (Nanotechnology Reviews, 2024)
Polydopamine coatings have been shown to allow to coat almost all materials with conformal films having a tunable thickness from a few up to more than 100 nm (and even more in some specific cases). These films are able to reduce metal cations, to be modified with many chemical moieties and advent hence as a “Holy Grail” in surface chemistry with an impressive amount of applicative papers published since 2007. However, the broad application field and ease of deposition from aqueous solutions hidden the complexity of the deposition mechanism(s). The discovery that polydopamine (PDA) films also form at air/water interfaces (in the absence of stirring or in stirring dependent manner) to yield membranes with physicochemical properties different than PDA films deposited at solid/water interfaces highlighted for the first time that the nature of the interfaces plays a major role in the PDA film growth mechanism and in the film properties. More recent research allowed to show that the surface chemistry of the used solid substrate modifies the composition of the thin deposited PDA film during the early stages of the deposition process with further deposition yielding to an almost substrate-independent PDA film. It is the aim of this review to describe complex surface effects occurring in PDA deposition and hence to complement other reviews which described the complexity of the chemistry yielding to PDA coatings.